Comparative study on quality awards - Basmenj, Fazlollah Agamohamadi; Sorooshian, Sharyar; Ismail, Md Yusof (American-Eurasian Network for Scientific Information, 2013)
Background: quality awards are known as one of the research interests in quality management sector. Objective: This study tries to compare quality awards. Results: In the first part we focused on Malaysian quality award, aim to introduce it as one of the successful quality awards systems. Then in the next phase of the paper we try to review the joint points and differences of the quality awards. Conclusion: Last section of this paper concludes the comparative study to improve quality awareness in the present increasing competitive world. © 2013 AENSI Publisher All rights reserved.